2019
DOI: 10.1098/rsif.2018.0966
|View full text |Cite
|
Sign up to set email alerts
|

The molecular chaperone Hsp33 is activated by atmospheric-pressure plasma protecting proteins from aggregation

Abstract: Non-equilibrium atmospheric-pressure plasmas are an alternative means to sterilize and disinfect. Plasma-mediated protein aggregation has been identified as one of the mechanisms responsible for the antibacterial features of plasma. Heat shock protein 33 (Hsp33) is a chaperone with holdase function that is activated when oxidative stress and unfolding conditions coincide. In its active form, it binds unfolded proteins and prevents their aggregation. Here we analyse the influence of plasma on the structure and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 71 publications
(125 reference statements)
1
30
0
Order By: Relevance
“…These modifications lead to the formation of the dimeric activated Hsp33. The unfolded region binds to unfolded proteins, avoiding their non-specific aggregation [ 43 , 92 ]. When oxidative stress is under control, Hsp33 releases the unfolded protein and returns to the reduced state.…”
Section: Adaptive Response Of Gram-negative Cells To Hoclmentioning
confidence: 99%
“…These modifications lead to the formation of the dimeric activated Hsp33. The unfolded region binds to unfolded proteins, avoiding their non-specific aggregation [ 43 , 92 ]. When oxidative stress is under control, Hsp33 releases the unfolded protein and returns to the reduced state.…”
Section: Adaptive Response Of Gram-negative Cells To Hoclmentioning
confidence: 99%
“…It is worth mentioning here that the extent of deleterious effects of plasmas are dependent on the enzyme. Some enzymes even exhibited increased activity after plasma treatment …”
Section: Resultsmentioning
confidence: 99%
“…Thus, in a study with plasma‐sensitive mutants, 87 genes were identified that possessed a protective function against a plasma that was applied for the treatment of bacteria‐containing solutions. [ 45 ] These genes encoded, for example, transcriptional factors to prevent DNA alkylation and initiate DNA repair mechanisms. Other genes encoded structural proteins involved in motility or biofilm formation as well as iron‐containing proteins involved in pathways such as respiratory electron transport chain.…”
Section: Discussionmentioning
confidence: 99%
“…Other genes encoded structural proteins involved in motility or biofilm formation as well as iron‐containing proteins involved in pathways such as respiratory electron transport chain. [ 45 ] In general, DNA strand breaks or DNA lesions possibly caused by modified nucleobases can be formed by (V)UV radiation or reactive species such as ozone or hydroxyl radicals. [ 46,47 ] Such effects were also described for plasma treatments using plasmid‐containing solutions [ 48 ] or plasmid solutions dried on glass carriers.…”
Section: Discussionmentioning
confidence: 99%